El mercado y la libertad contractual de los consumidores en los contratos por adhesión (2015)
The contract conceived in the framework of liberal individualism became the final result of an offer and acceptance process which was shaping the expression of two wills that seek to ensure their interests while seeking to seal the deal. However, the processes of mass production, the market economy, the technological developments and the consumer society generated transformations that led to the proliferation of a new contractual institution: the adhesion contract.